THE RESISTANCE EVALUATION OF THE LOAD-BEARING STRUCTURES ROLLING STOCK CYCLIC LOADS WITH THE INFLUENCE OF UNIFORM CORROSION - Gorobets, V. L.; Yagoda, D. O.; Yagoda, P. O. (Science and Transport Progress, 2008)
In conditions of long-term operation the bearing structures of a rolling stock are subject to action of an environment. It causes their uniform corrosion and decrease in bearing ability of the structures. The article is devoted to a technique of the account of uniform corrosion in problems of forecasting of a residual resource of railway structures.